Unheard & Ignored: Impact of COVID-19 Lockdown on Disadvantaged Children in Nepal - Pandey, Akash; Lama, Ashmita; Poudyal, Aassmi (International Journal of Social Sciences and Management, 2021)
The unprecedented situation brought about by the COVID-19 lockdown has affected the lives of children across the world. Although the information on COVID-19 impact on children is less heard and often ignored, its consequences will mark a ripple effect in the well-being of children, especially from disadvantaged backgrounds. This paper-based on secondary data explores the impacts induced by the COVID-19 lockdown on the lives of disadvantaged children in Nepal. The study has particularly discussed the problems faced by children from remote communities, children with disabilities, and children living in the streets. This study has firstly analyzed their existing situation through an extensive literature review followed by a detailed review of the impact and aftermath of the earlier crisis in those underprivileged lives and an outline of how the current pandemic can also trigger such repercussions in the coming periods. Findings show the different factors associated with intensifying the current problems experienced by the target groups. The study concludes with a recommendation to undertake primary research to highlight the problems from a much broader way so that the results can be implicated in a more scientific manner to grab the attention of policymakers and other relevant stakeholders to address the issue.